Game programming patterns - Nystrom, Robert, ....- (Lexington : Genever Benning, 2014)
Design patterns revisited -- Sequencing patterns -- Behavioral patterns -- Decoupling patterns -- Optimization patterns.
Keywords: Computer games; Programmering; Spelprogrammering